The Study of Learning Promotion’s Status for Developing Critical Thinking Skills in Media Literacy of Secondary Schools’ Students under Primary Educational Service Area in Chiang Mai - Wimolsittichai, Nilobon (Journal of Information Science Research and Practice, 2024)
Purpose: 1) To explore the status and the uses of learning resources of schools under Primary Educational Service Area in Chiang Mai and 2) To study the status and challenges of teaching and learning for developing critical thinking skills in media literacy of secondary schools’ students under Primary Educational Service Area in Chiang Mai Methodology: This study utilized a mixed-method approach, employing survey questionnaires and focus group interviews to ensure triangulation. Participants included school principals, teachers, and librarians teaching secondary students. A stratified random sampling of 330 schools’ representatives and a purposive sampling of 30 schools’ representatives were selected from 656 schools. Descriptive analysis, including frequency, percentage, mean, and standard deviation, was conducted, along with content analysis to categorize qualitative data into themes. Findings: The overall status of learning resources, the uses of learning resources, and teaching and learning for developing critical thinking skills in media literacy of secondary schools’ students under Primary Educational Service Area in Chiang Mai was moderate (x̄ = 3.42). Meanwhile, the overall challenge was low (x̄ = 2.16). The main challenges were insufficient information resources (x̄ = 2.31), administration (x̄ = 2.26), and students’ development (x̄ = 2.15). Both quantitative and qualitative findings indicated consistent challenges, particularly in information resources, administration, and school environment. Recommendations from school representatives focused on four themes: administration, learning materials, school staff, and collaborative networks. Application of this study: This study offers crucial insights into the status and challenges of learning resources, as well as their impact on fostering critical thinking skills in media literacy among secondary schools under Primary Educational Service Area in Chiang Mai. It forms part of a broader research project, the Enhancement of Developing Critical Thinking Skills in Media Literacy of Secondary Schools’ Students under Primary Educational Service Area in Chiang Mai in Education 4.0 Era. The findings provide a foundation for developing resource management guidelines and educational activities to enhance critical thinking. Moreover, the study highlights the significance of learning resources in shaping students' media literacy skills, vital for the 21st century.